Age-related hearing loss influences functional connectivity of auditory cortex for the McGurk illusion. (August 2020) - Rosemann, Stephanie; Smith, Dakota; Dewenter, Marie; Thiel, Christiane M.
Abstract: Age-related hearing loss affects hearing at high frequencies and is associated with difficulties in understanding speech. Increased audio-visual integration has recently been found in age-related hearing impairment, the brain mechanisms that contribute to this effect are however unclear. We used functional magnetic resonance imaging in elderly subjects with normal hearing and mild to moderate uncompensated hearing loss. Audio-visual integration was studied using the McGurk task. In this task, an illusionary fused percept can occur if incongruent auditory and visual syllables are presented. The paradigm included unisensory stimuli (auditory only, visual only), congruent audio-visual and incongruent (McGurk) audio-visual stimuli. An illusionary precept was reported in over 60% of incongruent trials. These McGurk illusion rates were equal in both groups of elderly subjects and correlated positively with speech-in-noise perception and daily listening effort. Normal-hearing participants showed an increased neural response in left pre- and postcentral gyri and right middle frontal gyrus for incongruent stimuli (McGurk) compared to congruent audio-visual stimuli. Activation patterns were however not different between groups. Task-modulated functional connectivity differed between groups showing increased connectivity from auditory cortex to visual, parietal and frontal areas in hard of hearing participants as compared to normal-hearing participants when comparing incongruent stimuli (McGurk) with congruent audio-visual stimuli. These results suggest that changes in functional connectivity of auditory cortex rather than activation strength during processing of audio-visual McGurk stimuli accompany age-related hearing loss.